Cyclist Safety and Comfort of Bicycle Facilities in the Bintaro Jaya During Covid-19 Pandemic Using Bicycle Level of Service - Fredy Jhon Philip Sitorus; Galih Wulandari Subagyo; Rio Yohanes Nikijuluw (Kadiri University, 2022)
Limited cycling facilities are one of the problems that often occur in urban areas in Indonesia, especially Bintaro Jaya, an area that cyclists often traverse during the COVID-19 period as it is today. The lack of service level of bicycle facilities on Jl. Boulevard Bintaro Jaya often causes bicycle users to feel less safe and comfortable during cycling. This study was conducted to know the service of bicycle facilities in Bintaro, especially on jl. Boulevard Bintaro Jaya. The most affecting factor of the service level of bicycle facilities in Bintaro is the high volume of traffic. One of the first steps to knowing the level of service of bicycle facilities is to analyze using the bicycle level of service (BLOS) method. In addition, a questionnaire will be conducted to determine the perception of bicycle facility users in Bintaro. Observations on traffic characteristics are carried out on weekdays and weekends, which are then to obtain BLOS data. Analysis was performed that BLOS values above 3.5 which mean the bike is not feasible for cyclists. The results concluded that the bicycle facilities in Bintaro Jaya are still not by the safety and comfort factors according to the BLOS method. To improve the safety and comfort of cyclists, the application of traffic calm such as speed hum is needed to reduce the impact of high traffic volume and high speed, repainting of markings and adding bicycle parking facilities.